Investigação sobre o uso da formulação transformada de Colebrook-White em canais circulares e naturais em escoamento uniforme - Albuquerque, Ícaro de França (2017)
The results of the expression for the calculation of permanent flow of water in pressurized tubes, such as Colebrook-White's expression, are very well-known for its good quality. However, this expression does not produce, in open channels, accurate results that could be judged as suitable for practical applications. The secondary currents and the presence of the free surface, that are linked to the transversal shape of the channels, are the factors attributed to the non-adequacy of pressurized tubes formulations to uniform flow in channels. For these reasons, methodologies that attempt to correct the additional effects of energy losses on uniform channel flow have been developed in recent decades and there were very encouraging results. Among these methodologies, it is highlighted in this dissertation, the formulation for calculation of the uniform flow in channels, which take into account the shape effects of the channels on the resistance to the flow, using applying the Colebrook-White equation. The application of the AC-W formulation for the calculation of the flow in channels in uniform flow in channels of prismatic sections, smooth and rough, has produced better results than the well-known Manning equation. In this work, the applications of the AC-W and Manning formulation for the flow calculation in smooth and rough circular channels and natural channels, in uniform flow, to experimental data obtained in the literature are carried out. Comparisons are made between these formulations based on the analysis of the results produced. As a way to verify the performance of the formulations, the calculated results are compared with those observed, using the criterion of the lowest absolute relative mean error (MARE) beside other indicators. The AC-W equation was more efficient for all applications, reaching only 28.1% of the MARE obtained with the Manning formula to the natural channels and 50.4% to the circular channels.